A Project study on the Knorr Department of California Manufacturing Corporation - Casibang, Cary; Mirabite, Josue; Vitriolo, Julito; Ramel, Arsenio; Cantoria Ming (College of Engineering, 1983)
The project study was primarily geared to expose the group to the real-world problems and situations in the various areas of production such as production planning and control, inventory, manufacturing procedures, plant and facilities lay-out, plant capacity analysis to name a few. Essentially, the group tried to put into effect the numerous esoteric theoretical concepts and formulations imparted to them in class in the investigation and analysis of the production system under study. Specifically, the actual production system of the California Manufacturing Corporation provided for the venue for such production system analysis. A basic problem encountered as the project study progresses is the gathering of relevant information. However, the interviews and plant visits conducted to be crucial in the study of the production system. To a large extent, this form of data-gathering facilitated the group's documentation and analysis of the system under study. In the process, many of the areas of interest were unfortunately classified as "restricted or confidential" from the modest amount of data collected, the analysis uncovered several problems including the existence of excessive distances between work-centers and machines, delays in production schedules and insufficient work space. The main problem however, centered primarily on the manufacturing area lay-out. As a result, inefficiencies in facilities and labor use and the coincident high costs become apparent. The analysis and problem-solving method using the CRAFT technique for evaluating plant lay-outs yielded re-layout as a major alternative. In addition, from the outcome of the CRAFT analysis, the group recommended that automation of the entire manufacturing area with the employment of the minimum necessary labor manpower will enable the company to continue their production processes efficiently and enable them to respond effectively to the rising market demands of their assorted product lines.